2014
DOI: 10.5539/gjhs.v7n1p1
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of the Impact of Service Quality on Patient Satisfaction in Private Hospitals, Iran

Abstract: Objective:Perceived service quality is the most important predictor of patient satisfaction. The purpose of this study was to investigate the impact of the service quality on the overall satisfaction of patients in private hospitals of Tehran, Iran.Method:This cross-sectional study was conducted in the year 2010. The study’s sample consisted of 969 patients who were recruited from eight private general hospitals in Tehran, Iran using consecutive sampling. A questionnaire was used for data collection; contactin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 38 publications
8
55
0
16
Order By: Relevance
“…Moreover, hospital managers and supervisors should identify the required standards and outstanding issues of hospital hospitality from the viewpoint of patients and the way it affects the patients. [20] Literature review showed that previous studies only addressed the physical aspects of hotel services such as environment, physical space, light, ventilation, and nourishment. However, the present study examined 11 dimensions of hotel services and the human, performance, financial, economic, cultural, and personnel identification dimensions were not studied in any of the previous researches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, hospital managers and supervisors should identify the required standards and outstanding issues of hospital hospitality from the viewpoint of patients and the way it affects the patients. [20] Literature review showed that previous studies only addressed the physical aspects of hotel services such as environment, physical space, light, ventilation, and nourishment. However, the present study examined 11 dimensions of hotel services and the human, performance, financial, economic, cultural, and personnel identification dimensions were not studied in any of the previous researches.…”
Section: Discussionmentioning
confidence: 99%
“…In medical sciences, one of the central principles of the charter of human ethics is respecting the dignity of the patient. [1920] In fact, dignity is closely linked to privacy, respect, independence, and control. [21] The Ministry of Health and Medical Education of Iran in 2010 implemented the patients’ rights in five topics, including the right to receive quality services, the right to receive appropriate information, the right to choose and decide, the right to receive health services, the right to privacy and confidentiality, and the right to access an effective complaints service to all its affiliated centers.…”
Section: Discussionmentioning
confidence: 99%
“…If the delivered service exceeds promises made, the consumer may react with positive emotions resulted in high emotional satisfaction. Goal-directed emotions on the other hand are emotions whereby consumer consciously seeks to experience [17] This opinion was supported by Zarei et al, [18] that stated, services that are characterized by strong goal-directed positive emotions are particularly important since experiential emotions may constitute the main outcome of the service and because of service variability, consumer perceived service quality and experience emotions might vary depending on the situation or service that they have encountered.…”
Section: Emotional Satisfactionmentioning
confidence: 92%
“…The study then concluded that there is a significant relationship between emotional satisfactions with customer loyalty as emotions can influence the decision making of a person. Consequently, positive emotions can influence customers to stay and being loyal whereby negative emotions could result in complaints and customers no longer use the products and services [18,20,21] …”
Section: Emotional Satisfactionmentioning
confidence: 99%
“…Utvrdili su znatnu povezanost između kvalitete usluga i zadovoljstva pacijenata, pri čemu su "troškovi usluga", "kvaliteta procesa" i "kvaliteta interakcija" imali najveći utjecaj na sveukupno zadovoljstvo pacijenata 35 .…”
Section: Pregled Dosadašnjih Istraživanja U Području Mjerenja Kvaliteunclassified